Measurement of the ethical organizational climate in higher education institutions - Maria Camila Bermeo-Giraldo; Alejandro Valencia-Arias; Iván Alonso Montoya Restrepo; Luz Alexandra Montoya Restrepo; Jackeline Valencia Arias (Institute of Advanced Engineering and Science, 2026)
Assessing the ethical climate in higher education institutions (HEIs) is essential, given their role in training future professionals and promoting social responsibility, academic integrity, and transparency. This study used a quantitative, cross-sectional approach to assess the ethical climate perceived by 150 students at a private university in Medellín, Colombia. Based on Victor and Cullen’s six-dimensional model, and using exploratory factor analysis and Cramer’s V statistic, significant associations were identified. In particular, positive relationships were found between rule-based and law/code-based ethical climates and perceptions of institutional efficiency. Likewise, a relationship was found between the dimensions of independence and care, such that students who act based on their own moral judgment appreciate supportive institutional environments. In addition, 65% of students value autonomy (independence), 43.2% prioritize compliance with legal norms (laws and codes), and 33.33% emphasize following strict rules (rules). These findings highlight the importance of both personal ethical values and external regulatory frameworks in the formation of ethical perceptions. Similarly, the results contribute practical guidance for HEIs managers to strengthen ethical leadership and institutional policies, promoting a more transparent and efficient academic environment. It is recommended that HEIs implement policies that strengthen ethical leadership and promote an organizational climate that favors ethical decisions and compliance with standards.